PENGARUH PENYULUHAN PERAWAT TERHADAP PERILAKU PENGGUNAAN MASKER PADA KARYAWAN DI PT. INDONESIA TRI SEMBILAN - Muhith, Abdul; Yanti, Jumaiyah Eka (SEKOLAH TINGGI KESEHATAN MAJAPAHIT MOJOKERTO, 2016)
One of the dust control which is produced by industry is using personal protective equipment of mask. Object of this study was to determined the effect of behavioral counseling on the use of mask to employees. The design of this study was used Quasy â Experimental. The population in this study were employees of PT. Indonesia Tri Sembilan. The study sample consisted of 18 respondents who met the inclusion criteria, divided into 2 groups : the treatment group and the control group, each group consist of 9 respondents. The independent variable in this study was counseling. The dependent variable in this study was the employee behavior on used of mask. Data collection used questionnaires and observation. Data analysis used Wilcoxon Signed Rank Test and Mann Whitney U Test. Result of Wilcoxon Signed Rank Test showed a significance value of knowledge ( p ) = 0.011, attitude ( p ) = 0.018, action ( p ) = 0.011 and the test results of the Mann Whitney U Test showed a significance value of knowledge ( p ) = 0.020, attitude ( p ) = 0.010, action ( p ) = 0.000, which means there was the influenced of illumination to the improvement of knowledge, attitudes and actions on employee used of mask. The proper practice of using mask is one of effective alternative interventions for maintaining employee health from diseases caused by dust. It was recommended that company should improve supervisory, apply discipline and provide more counseling on using of mask.Keywords : Counseling Nursing, Mask, Employee